Kendrick Lamar’s Criticism of Systemic Racism in the Album To Pimp a Butterfly - Pesonen, Joel (My University, 2025)
This thesis examines how Kendrick Lamar criticizes systemic racism in his album To Pimp a Butterfly. At the time of making this album in the 2010s systemic racism was a highly discussed topic and the tension related to the problem was on the rise, especially in the U.S. Examining Kendrick Lamar’s writing on the album gives a comprehensive look of the effects that systemic racism has on individuals and on a more societal scale. Lamar writes about his life as a Black male in the U.S. and how the oppression has followed him and the people around him throughout his life. There are parts in the album that concentrate more on the experiences Lamar endured in his adolescence and parts more about his life as of now as a successful music artist. Both experiences share the obstacles and struggles that systemic racism causes. Kendrick Lamar makes it clear that no matter the status, these effects cannot be escaped in his life and in To Pimp a Butterfly. In this thesis I will do a literary review of the album and discuss how Lamar wrote one of the most acclaimed albums of all time and at the same time an introspective story of the impact racism has in the U.S. To Pimp a Butterfly humanizes the experiences that millions of people face because of racism and brings awareness to the issue. The track, “Alright” from the album is proof of the effect the album has had and since 2015, it has been a civil rights anthem in various events. Still to this day in 2025 the discussion around the topics brought up in To Pimp a Butterfly are ongoing and Kendrick Lamar has made an album that will be topical for as long as people suffer from racism in the U.S.
Keywords: racism, systemic racism, rap, Kendrick Lamar